Nazi chic? : Fashioning women in the Third Reich - Guenther, Irene 1954- (Berg, 2004)
Introduction -- The fashion debate in World War I -- The "new" woman -- Fashioning women in the Third Reich -- "Purifying" the German clothing industry -- Germany's National Fashion Institute -- The war years -- Conclusion